Coordination for policy in transition countries - Musa, Anamarija (Mednarodna revija za javno upravo, 2015)
The formulation and implementation of public policy depends on the coordination capacities. In recent decades the need for coordination has increased due to the fragmentation caused by NPM reforms, decentralisation processes, the proliferation of the cross-cutting issues, as well as increased globalisation, Europeanisation, and professionalization. The coordination problem in Croatian administration, similarly to other transition countries, is critically important but understudied. This paper is based on a preliminary research on coordination in Croatian public administration with regard to policy formulation and implementation of three policies % regional development policy, anticorruption policy and e-government policy, based on the interviews conducted with higher civil servants and public officials. A special emphasis is given to the role which various actors play in coordination, as well as the structures Government employs in order to coordinate. The research shows that the development of coordination instruments in Croatia suffers from inefficiencies and is greatly influenced by politically driven considerations.
Keywords: anti-corruption policy; Croatia; e-government policy; e-vladna politika; Hrvaška; javna politika; protikorupcijska politika; public policy; regional development policy; regionalna razvojna politika